126k views
1 vote
Find

h ′(2), given that f(2) = −3, g(2) = 4, f ′(2) = −2,and g ′(2) = 5.

I only need help with part d (picture attached)

Find h ′(2), given that f(2) = −3, g(2) = 4, f ′(2) = −2,and g ′(2) = 5. I only need-example-1

1 Answer

7 votes

Answer:
-(1)/(2)

=========================================================

Work Shown:

Apply the quotient rule


h(x) = (g(x))/(1+f(x))\\\\h(x) = (A)/(B)\\\\h'(x) = (A'*B-A*B')/(B^2)\\\\h'(x) = (g'(x)*(1+f(x))-g(x)*(1+f(x))')/((1+f(x))^2)\\\\h'(x) = (g'(x)*(1+f(x))-g(x)*f'(x))/((1+f(x))^2)\\\\h'(2) = (g'(2)*(1+f(2))-g(2)*f'(2))/((1+f(2))^2)\\\\h'(2) = (5*(1-3)-4*(-2))/((1-3)^2)\\\\h'(2) = (-2)/(4)\\\\h'(2) = -(1)/(2)\\\\

User Arnp
by
7.1k points